2016
DOI: 10.1038/srep36900
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism and Energy Basis of Conformational Diversity of Antibody SPE7 Revealed by Molecular Dynamics Simulation and Principal Component Analysis

Abstract: More and more researchers are interested in and focused on how a limited repertoire of antibodies can bind and correspondingly protect against an almost limitless diversity of invading antigens. In this work, a series of 200-ns molecular dynamics (MD) simulations followed by principal component (PC) analysis and free energy calculations were performed to probe potential mechanism of conformational diversity of antibody SPE7. The results show that the motion direction of loops H3 and L3 is different relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…The Rg time graph showed that residual backbone and the folding of the receptor protein were steadily stable after the binding of inhibitors, which confirmed our results (Hassan et al, 2018). The RMSF value provides a better understanding of the protein flexibility and structural fluctuations (Chen et al, 2016;Mahapatra et al, 2018). To define the flexible regions of the enzyme in the enzyme-substrate/inhibitor complexes, the RMSF values of Cα atoms of the protein were evaluated.…”
Section: Molecular Docking and The MD Simulation Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…The Rg time graph showed that residual backbone and the folding of the receptor protein were steadily stable after the binding of inhibitors, which confirmed our results (Hassan et al, 2018). The RMSF value provides a better understanding of the protein flexibility and structural fluctuations (Chen et al, 2016;Mahapatra et al, 2018). To define the flexible regions of the enzyme in the enzyme-substrate/inhibitor complexes, the RMSF values of Cα atoms of the protein were evaluated.…”
Section: Molecular Docking and The MD Simulation Analysissupporting
confidence: 81%
“…Finally, the PMF pattern was provided by the Weighted Histogram Analysis (WHAM) method, which was carried out by GROMACS as "g_wham" command (Zeng et al, 2016). Moreover, for a better recognition of the MD process, the RMSF (root mean square fluctuation) (Chen et al, 2016;Mahapatra et al, 2018), RMSD (root mean square deviation) (Kaur et al, 2019;Shen et al, 2012), Rg (Radius of gyration) (Anantram et al, 2018;Farasat et al, 2017;Lobanov et al, 2008), the inhibitor and substrate distance from the amino acids of the enzyme active site (Corvo et al, 2013;Kato et al, 2017), and the van der Waals and the electrostatic energy of each system were analyzed using GROMACS tools in the period of simulation (Fried and Boxer, 2017;Schutt et al, 2015). Eventually, the final PDB file of MD simulation was plotted using Pymol software (Stourac et al, 2019).…”
Section: Pmf Analysis Of the Enzyme-substrate And Enzyme-inhibitor Comentioning
confidence: 99%
“…The results showed that RMSD value of the Calprotectin alone was greater than the Calprotectin-UFAs complexes which confirms the structural changes of the Calprotectin in presence of fatty acids. RMSF value provides a better understanding of the protein flexibility and structural fluctuations [37,38]. To study the Calprotectin flexibility in presence of AA and OA, the RMSF value was calculated for Calprotectin, Calprotectin-AA and Calprotectin-OA during the simulation.…”
Section: Molecular Docking and MD Simulation Analysismentioning
confidence: 99%
“…RMSF comprises a valuable parameter which allows for a more proper understanding of protein flexibility and structural fluctuations (Chen et al., 2016 ; Mahapatra et al., 2018 ). RMSF was calculated to evaluate the flexibility of the S2 protein in the presence or absence of the peptide (Enf).…”
Section: Resultsmentioning
confidence: 99%